Systematic risk of stock returns in Asian emerging markets:decomposition determinants. - Hooy , Chee Wooi (Universiti Sains Malaysia, 2014)

(untitled)
This project studies decomposition from stock returns to systematic risk of listed firms in Asian emergin markets.Our main contribution is to revisit the country versus debate in international diversification debate using decomposition of systematic risk.We provide justifications to investigate from systematic risk perspective and compare to total risk decomposition suggested by other researchers.